PENERAPAN PEMBELAJARAN KOOPERATIF TPS TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DI KELAS XI - Siti Suleha Lubis (JURNAL MathEdu (Mathematic Education Journal), 2018)
Abstract This study aims to 1) describe of using TPS learning model, 2) describe the average of students’ mathematical communication ability before and after using TPS learning model, and 3) know whether there is a significant influence of using TPS learning on students’ mathematical communication ability. The research was conducted at the eleventh grade students of SMA Negeri 3 Panyabunagan by applying experimental method (pretest post test one group design) with 25 students as the sample and they were taken by using random sampling from 113 students. Observation and test were used in collecting the data. Based on the data analysis, it was found that: (1) the average of using TPS learning model was 3.21 (good category) and (2) the average of students’ mathematical communication ability before using TPS learning model was 44.22 (fail category) and after using TPS learning model was 80.3 (very good category). Furthermore, based on inferential statistic by using paired sample ttest and helping SPSS 16, the result showed the significant value was less than 0.05 (0.000<0.05). It means, there is a significant influence of using TPS learning on students’ mathematical communication ability at the eleventh grade students of SMA Negeri 3 Panyabunagan. Key words: TPS learning model, students’ mathematical communication ability